2022
DOI: 10.1111/jocs.16666
|View full text |Cite
|
Sign up to set email alerts
|

The effect of tracheostomy on extracorporeal membrane oxygenation outcomes

Abstract: Introduction The optimal timing for pursuing tracheostomy in patients with prolonged mechanical ventilation with either veno‐arterial (VA) or veno‐venous (VV) extracorporeal membrane oxygenation (ECMO) is a discussion of risk versus benefit. Depending on the etiology, cardiothoracic surgical patients carry some of the highest risk for respiratory failure postprocedure. Given that patients with end‐stage cardiopulmonary status may be fraught with substantial comorbidities, it is critically important to manage t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Tracheostomies have been proven to be an effective treatment for various critically ill patients in recent years [ 15 , 17 , 45 ]. For patients undergoing high-risk surgeries, such as cardiovascular procedures, performing tracheostomies at an optimal time point when needed may significantly improve their prognoses [ 3 , 8 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tracheostomies have been proven to be an effective treatment for various critically ill patients in recent years [ 15 , 17 , 45 ]. For patients undergoing high-risk surgeries, such as cardiovascular procedures, performing tracheostomies at an optimal time point when needed may significantly improve their prognoses [ 3 , 8 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, 35 patients (35.7%) underwent tracheostomy during ECMO with no intergroup differences, and our subgroup analysis showed that early tracheostomy was associated with favorable patient outcomes similar to those in subgroups who received tracheostomy during or after ECMO. A recent single-center, retrospective, observational study of 54 patients receiving ECMO in the United States of America compared the complications of tracheostomy during ECMO with those after ECMO removal in detail [ 22 ]. Major complications, such as bleeding requiring intervention and aspiration, were equivalent; however, minor complications, including oozing and mucous plugging, were significantly more frequent in patients undergoing tracheostomy during ECMO (65.5 vs. 32.0%).…”
Section: Discussionmentioning
confidence: 99%
“…It is generally required that mechanical ventilation is continued during ECMO, and tracheostomy is performed in 18–51% of patients undergoing ECMO [ 16 18 ]. Recently, some studies have examined and reported on the procedures and complications associated with tracheostomy [ 19 22 ], however, there is a lack of evidence regarding the impact of tracheostomy timing on patient outcomes in patients receiving ECMO.…”
Section: Introductionmentioning
confidence: 99%
“…11 A recent single-center observational study of 92 patients by Grasselli et al, receiving ECMO (87% venovenous ECMO), in whom infections were systematically and prospectively identified through the application of well-established clinical practice guidelines, 12,13 reported high rates of NIs (55%), with VAP and multidrug-resistant organisms, found to be common. 14 Those who acquired NIs had higher overall mortality, longer mechanical ventilation, and ECMO durations, and spent longer in the ICU. Younger age (2-35 years old) was independently associated with a higher risk of NIs.…”
Section: Ni Associated With Ecmomentioning
confidence: 97%
“…• Consider early tracheostomy in adult patients. 14 • Early and complete enteral nutrition should be used.…”
Section: Prevention Of Systemic Infectionsmentioning
confidence: 99%